Relationship between family functioning and affiliate stigma in parents of children with autism spectrum disorder in China: the mediating role of positive aspects of caregiving - Du, Xiaoyan; Su, Xiangdan; Ding, Dandan; Zhu, Yiru; Sun, Yongrong; Wang, Miaomiao; Xiao, Yang; Xu, Haiping (Frontiers in Psychiatry, 2025)
ObjectiveThe present research was conducted to examine whether family functioning is related to affiliate stigma in Chinese caregivers of children with autism spectrum disorder (ASD) and how positive aspects of caregiving affect this relationship.MethodsTwo hundred and six caregivers of children with ASD were investigated using the Family APGAR scale, the Affiliate Stigma scale, and the Chinese version of the Positive Aspects of Caregiving scale. The statistical methods of Pearson correlation analysis and mediation effect analysis were used to statistically analyze the relationship between family functioning, affiliate stigma and positive aspects of caregiving.ResultsThe results indicated that family functioning and positive aspects of caregiving were negatively associated with affiliate stigma and that family functioning was positively correlated with positive aspects of caregiving. Furthermore, positive aspects of caregiving partially mediated family functioning and affiliate stigma.ConclusionThese findings suggest that family functioning can directly influence the affiliate stigma of caregivers of children with ASD and indirectly influence affiliate stigma through positive aspects of caregiving.